Predictive Factors for Regression versus Progression of Nonevacuated Posttraumatic Acute Extradural Hematoma - Elkholy, Hany; Elnoamany, Hossam; Hussein, Mohamed Adel (Asian Journal of Neurosurgery, 2024)
Study Design This study was a retrospective study conducted from October 2020 to October 2022 on 106 posttraumatic patients with acute extradural hematomas (EDHs) who were initially planned for conservative treatment. 74 patients had spontaneous EDH regression (EDHR), while 32 patients developed EDH progression (EDHP) and were shifted for surgery. The two groups were statistically compared regarding the different demographic, clinical, and radiographic factors to identify the significant predictors for regression versus progression of acute posttraumatic EDH.Objectives Conventionally, urgent evacuation is the accepted management for EDH. However, several recent reports have described successful conservative management in selected patients. There are no adequate clues to verify patients who will have spontaneous EDHR from those at risk for EDHP and delayed surgery. The main objective of this study was to identify the significant predictors for possible regression versus progression of acute posttraumatic EDH initially planned for nonsurgical treatment.Materials and Methods A retrospective study conducted over 2 years, included 106 head trauma patients with acute EDH, who were admitted to our department and were initially planned for conservative treatment. Various demographic, clinical, and radiographic factors were analyzed to verify the significant predictors for spontaneous EDHR (EDHR group) versus EDHP and subsequent surgical evacuation (EDHP group).Results The mean age was 20.37 ± 12.712 years and the mean Glasgow Coma Scale score (GCS) was 12.83 ± 2.113. Total 69.8% of patients showed spontaneous EDHR, while 30.2% developed EDHP and were shifted for surgical evacuation. Statistical comparison showed that higher GCS (p = 0.002), frontal location (p = 0.022), and concomitant fissure fracture (p =  0.014) were the significant predictors for EDHR, while younger age (p = 0.006), persistent nausea/vomiting (p = 0.046), early computed tomography (CT) after trauma (p = 0.021), temporal location (p < 0.001), and coagulopathy (p = 0.001) were significantly associated with EDHP.Conclusion Patients with traumatic EDH fitting the criteria of initial nonsurgical treatment necessitates 48 hours of close observation and serial CT scans at 6, 12, 24, and 48 hours to confirm the regression or early detect the EDHP. Patients with high GCS, frontal hematomas, and associated fissure fracture are at low risk for EDHP. Increased alertness is mandatory for young age and patients with persistent nausea/vomiting, early CT scan, temporal hematomas, or coagulopathy.
Keywords: head injury; extradural hematoma; conservative management; surgical evacuation; progression